STUDENTS’ PERCEPTIONS ON THE USE OF TIKTOK APPLICATION FOR DIGITAL STORYTELLING AS SPEAKING LEARNING MEDIA - FEBLIANSYAH, MUHAMMAD; SYAFRYADIN, SYAFRYADIN (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2023)
This study examined how students perceived using the less well-known and understudied TikTok application for digital storytelling in their combined learning. This research was conducted using a quantitative method. One of the Senior High Schools in Bengkulu recruited a sample of 19 students from the 12th grade. The Likert scale was used to do a quantitative analysis of it. The study's findings indicated that most students had a favorable opinion of using the TikTok application to help them learn how to speak. They had positive feelings about Tiktok. They thought of tiktok as an engaging, fascinating, inspiring, and enjoyable learning tool. Based on how the students felt utilizing TikTok affected them, TikTok was the ideal learning tool for them. Additionally, Tiktok had an impact on the students' utilization of a variety of features and tools in an application for digital storytelling. It demonstrated that the pupils gave the learning process more consideration. Based on the findings, the researchers fervently advised teachers to start using Tiktok to learn English, especially for speaking.